Out-of-office blood pressure measurement for the diagnosis of hypertension in pregnancy: Survey of Canadian Obstetric Medicine and Maternal Fetal Medicine specialists. (March 2020) - Tran, KC; Potts, J; Robertson, J; Ly, K; Dayan, N; Khan, NA; Chan, W
Background: Multiple hypertension guidelines recommend out-of-office measurements for the diagnosis of hypertension in non-pregnant adults, whereas pregnancy guidelines recommend in-office blood pressure measurements. The objective of our study was to determine how Canadian Obstetric Medicine and Maternal Fetal Medicine specialists measure blood pressure in pregnancy. Methods: An email survey was sent to 69 Canadian Obstetric Medicine and Maternal Fetal Medicine specialists in academic centers across Canada to explore the practice patterns of blood pressure measurement in pregnant women. Results: The response rate was 48%. The majority of respondents (63.6%) preferred office blood pressure measurement for diagnosing hypertension, but relied on home blood pressure readings for ongoing monitoring and management of hypertension during pregnancy (59.4%). The preferred method of out-of-office blood pressure measurement was home monitoring; 24-hour ambulatory blood pressure monitoring was not used due to limited availability and cost. Conclusions: There is wide practice variation in methods of measuring blood pressure among Canadian specialists managing hypertension in pregnancy.